Universal scaling relations for the rational design of molecular water oxidation catalysts with near-zero overpotential - Garcia Melchor, Max; Schmitt, Wolfgang (My University, 2019)
A major roadblock in realizing large-scale production of hydrogen via electrochemical water splitting is the cost and inefficiency of current catalysts for the oxygen evolution reaction (OER). Computational research has driven important developments in understanding and designing heterogeneous OER catalysts using linear scaling relationships derived from computed binding energies. Herein, we interrogate 17 of the most active molecular OER catalysts, based on different transition metals (Ru, Mn, Fe, Co, Ni, and Cu), and show they obey similar scaling relations to those established for heterogeneous systems. However, we find that the conventional OER descriptor underestimates the activity for very active OER complexes as the standard approach neglects a crucial one-electron oxidation that many molecular catalysts undergo prior to O–O bond formation. Importantly, this additional step allows certain molecular catalysts to circumvent the “overpotential wall”, leading to enhanced performance. With this knowledge, we establish fundamental principles for the design of ideal molecular OER catalysts.
PUBLISHED
Keywords: Water oxidation; Oxygen evolution; Density functional theory; Scaling relations; Reaction descriptors; Catalyst design